Full D-Band GaN Power Amplifier MMIC and Waveguide Module - Cwiklinski, Maciej; Riedmann, Nico; Ziegler, Robert; Vossiek, Martin; Bruckner, Peter; Schwantuschke, Dirk; Mikulla, Michael (2024 19th European Microwave Integrated Circuits Conference, EuMIC 2024, 2024)
In this article, we present a gallium nitride (GaN) power amplifier (PA) monolithic microwave integrated circuit (MMIC) and waveguide module that cover the full D-band (110-170 GHz) with a state-of-the-art performance. On-wafer measurements of the balanced ten-stage GaN PA show a small-signal gain of more than 13 dB over the full D-band and a peak output power of 22.6 dBm at 160 GHz. A two-way waveguide module delivers more than 18.5 dBm of output power over the full D-band with a peak of 25 dBm at 120 GHz. To the best of our knowledge, the reported amplifiers show the highest output power within GaN-based circuits beyond 140 GHz. This is also the first demonstration of GaN PAs covering the full D-band.
CRIS-Team Scopus Importer:2024-12-13
Keywords: Broadband; D-band (110-170 GHz); gallium nitride (GaN); high-electron-mobility transistor (HEMT); monolithic microwave integrated circuit (MMIC); power amplifier (PA); waveguide module